The Effect Of Solar System Scope Learning Media on Student’s Learning Outcomes In The Solar System Material - Silviani Sembiring; Melva Silitonga (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2026)
This study aims to determine the learning outcomes of students who use the Solar System Scope, to determine the learning outcomes of students who use conventional learning media, and to determine the effect of using the Solar System Scope on student learning outcomes in the Solar System subject. This study was conducted at the UPT SMP Negeri 29 Medan from November 2025 to February 2026. The research design used was quantitative research with a quasi-experimental method with a non-equivalent pretest-posttest control group design. The study population consisted of all seventh-grade students at UPT SMP Negeri 29 Medan, which consists of 8 classes. The research sample was selected using purposive sampling, with Class VII-6 as the experimental class and Class VII-7 as the control class, totaling 64 students. The research instrument consisted of a multiple-choice test with 20 questions to measure students' cognitive learning outcomes. The results of the study showed that the average pretest score of the experimental class increased from 61 to 79 in the posttest, while the score of the control class increased from 51 to 72. The results of the independent sample t-test showed a significance value of 0.002 < 0.05 with a calculated t-value of 3.322. Based on these results, it can be concluded that the use of Solar System Scope learning media has a significant influence on student learning outcomes in the Solar System material.